Egodocuments Publishing in Lithuania 1991–2015: Published Letters and Diaries of Vytautas Kubilius - Dautartienė, Margarita (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; summary in English] Publication provides an analysis of egodocuments (sensu stricto) publishing in Lithuania from XX century 10 decade to XXI century. Changes in society brought by XX century transformed publishing process and literature field. 5 publishing houses owned by the government („Vaga“, „Vyturys“, „Mintis“, „Mokslas“, „Šviesa“) were accompanied by many private enterprises, which instantly responded to the reader’s request of such publications, which in Soviet times were not available or had never been published because of ideological censorship. At the 9 decade of XX century autobiographical writing, autobiographical cultural practices became very popular. This happened mainly because of tendency for individual to witness history, be a part of historical events. The dissemination of egodocuments through traditional and digital publishing, participation in social networks becomes important storage of cultural memory and object of scientific research. Vytautas Kubilius‘s published letters and diaries demonstrates publishing tendencies of Lithuania and the context of egodocument’s publishing.